TECHNICAL AND ECONOMICAL FEASBILITY IN THE OPERATION OF RAFT CATAMARAN OF KRISHNAPATNAM COAST, ANDHRA PRADESH - A. Balasubramanian; K. Dhanapal; P. Jawahar (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Fishing with low energy receives considerable significance in India. It utilizes the indigenous resources with less expenditure. A survey was conducted at Krishnapatnam coast of Andhra Pradesh to study the technical and economic feasibility of traditional crafts used in this region. However, in this paper, significance was given only to raft catamaran since it is one of the popular traditional crafts of this coast. The study dealt with various aspects like design of raft catamaran, its size, and material used for fabrication, mechanization, type of gears operated from this craft, various fishing methods and its economics. The predominant size of the raft catamaran existing in this region is 6 logged and 9 m Over All Length (OAL). This study further describes the fishery, season of operation and various costs and returns involved in the operation of the crafts. The input and output ratio of fishing craft was 1:1.57. Problems and remedial measures required for the development of low energy fishing techniques are discussed with some suggestions.